The Effect of Four Weeks of Home-Based Exercise Program with Unstable Sandals Functional Indicators Related to Falls in Older Men - Seyedi Bidgoli, Seyed Mohamad; Rajabi, Hamid; Abbasi, Ali (Journal of Clinical Physiotherapy Research, 2023)
Introduction: Due to the population growth rate, Iran will face an aging explosion soon. Thus, maintaining functional independence and fall prevention should be considered as the main policy concerns in caring for this group. Therefore, the aim of the present study was to investigate the effects of training with unstable sandals on some functional indicators related to falls in healthy elderly men prone to falls during the corona epidemic. Materials and Methods: In this quasi-experimental study with pre-test and post-test design, 42 elderly men who were prone to fall (age: 70.69±4.11 years, height: 174.12±6.07 cm, weight: 73.29±7.58 kg, BMI: 24.2±2.42 kg/cm2) with some diagnostic performance indicators were selected from 61 elderly people and divided into three groups of 14 people. One group performed home exercises with unstable sandals, the second group performed these exercises with stable sandals, and the control group was engaged in their normal life and did not participate in any exercise training intervention. The training course was performed in three sessions per week on non-consecutive days for four weeks. Before and after the training session, participants were assessed using the Berg Balance Scale, Timed Up & Go, Functional Reach Test, and 30-second stand chair. Results: Analysis of variance with repeated measures showed a significant difference in all performance tests of both training groups compared with the control group after 4 weeks of training (P<0.001). There was a significant improvement in the unstable sandal group in the Berg Balance Scale and Timed Up & Go tests with a progress of 12.3% and -27.1% compared with the pretest, and 8.5% and -21.1% compared with the stable sandal group (P<0.05). Despite the improvement in Functional Reach and 30-s stand-chair tests in the unstable sandal group compared with the stable sandal group, no significant difference was observed between them (P≥0.05). Conclusion: Using unstable sandals in a home exercise protocol as an overload training tool for greater improvement in healthy elderly men who are prone to falls can effectively improve some static and dynamic performance indicators, but it has no effect on increasing the strength of the lower limbs.